Anatomical and Sexual Functions at Post Neovagina operation on Mayer Rokitansky Kuster Hauser Syndrome (MRKH) Patients with Sigmoid ,Amnion and Conventional Methods in Dr. Soetomo Hospital - Uning Marlina; Hari Parathon; Azami Demas; Jimmy Yanuar; Iwan Kristian (Universitas Muhammadiyah Surabaya, 2020)
ABSTRACT Background: The Mayer–Rokitansky–Kuster–Hauser (MRKH) syndrome is congenital malformation due to utero‐vaginal agenesis. For many years Dr Soetomo Hospital has been applying McIndoe technique using biomaterial amnion. Recently, in collaboration with digestive surgery, neovagina operation using sigmoid was performed. However, no data are available on the complications, anatomic, and functional results of the neovagina operation using sigmoid and amnion. Methods: MRKH patients who have performed neovagina operations from January 2011 to December 2014 were involved in this case review. The anatomical function was measured based on minimal vaginal length of more than 6 cm and width of 3 cm, while sexual performance is measured by Female Sexual Function Index (FSFI), which is above 23, and Female Sexual Distress Score Revised (FSDSR), whose score is < 11. Result: In 4 years period, there were 6 cases of MRKH underwent neovagina (1 used sigmoid and 5 used amnion) at Dr Soetomo Hospital. All of them had a satisfying anatomical and sexual function. Even though neovagina operation significantly reduces sexual distress, but it does not necessarily mean alleviate as seen by the high FSDSR score. Neovagina using amnion has faster operation time and cheaper with the same length of hospital stay than sigmoid neovagina. Sigmoid neovagina has a better vaginal length, lubrication and no need dilatation after operation, but it has higher complication risk. Conclusion: The Neovagina technique should be used at Soetomo Hospital depends on patient wishes and circumstances. For those who have strong financial support and are not willing to do manual dilatation, they should use the sigmoid neovagina, while those who are able to do manual dilatation, then the amnion neovagina is a good choice.Keywords: Neovagina, MRKH, sigmoid, amnion, anatomic function